Pendampingan Industri Pengolahan Telur Asin di Desa Pendem Kecamatan Junrejo Kota Batu - Ardik Praharjo; R. Iqbal Robbie (LPPM UNINUS, 2020)
Society in general requires an activity to increase income and productivity. The importance of cooperation between citizens in realizing these desires must be in line and supported by the Village Government, so that the development planning process can run optimally. The desire of residents who are accommodated by the Village Government generates ideas to form a Tourism Village that is packaged in the theme